Sustainability Business Model to Tackle Energy Transition and Meeting Future Challenges - Ghosh, Indranil (Indian Journal of Power and River Valley Development, 2023)
Can a Business Model become an useful tool for the Managers of the Indian Power sector to meet the challenges arising out due to energy transition? Probably, “Winners Sustainability Model©”, a management tool developed with the sole intention of Business Sustainability, may be helpful in strategizing and converging the efforts towards this. Based on the varied training and consultancy experience, the author has developed a generic Business Excellence model or a Sustainability Framework and named it as “Winners Sustainability Model©” to address sustainability issues of the businesses. This model, rather framework, can be used to address and assess the change related issue. The model also supports energy related strategy supporting innovation, Learning and Development, Legal and Regulatory etc. This model can be an integral part for the development of the corporate business strategy and can be percolated down further as lead and lag measurement parameters in the corporate Balance Score Card or unit level SMART objectives and even up to KRA and KPI of the individuals so that efforts towards any ensuing change can be focused effectively. This model provides a framework for effective deployment and also can be used as an ‘Assessment Tool’, which shall be able to find out Opportunities for Improvement and Non-Conformity along with their impact levels adequately. The Application of the model shall follow the following important steps: 1. The model is incorporated from the Strategy Development phase itself. Considering the model as a framework, the management of the organization and the assessors agree on a protocol. The protocol points become the parts of the business strategy. 2. The next step is the deployment of strategy. The organization ensures implementation of the protocol points with sanctity. 3. Third major step is assessment or audit. The protocol is used to pinpoint the positioning of the organization for the sustainability per se. The assessment report will contain the following: S – Strength; C – Conformity; OFI – Opportunities for improvement; NC – Non-conformityImpact level of the non-conformities as “High”, “Medium” and “Low” and NC closure activities as “Easy” and “Difficult” 4. After this, the organization may even go for a compliance audit/assessment 5. There may be possible benchmark of performance for each of the categories included in the framework. The framework of the Winners’ Sustainability Model© is divided into 10 (ten) distinctive Non-finance Modules. The Modules of the Model (or Framework) are as follows: Module 1 - Leadership and Governance (L&G) Module 2 - Legal nd regulatory requirements/compliance (C) Module 3 - Risk assessment (RA) Module 4 - Work and Organization Management (WM) Module 5 - Occupational Safety (OS) Module 6 - People’s competency/learning and development (L&D) Module 7 – Human Focus Module 8 – Environment Module 9 - Corporate Social Responsibility (CSR) Module 10 – Operational & Business Excellence Almost all modules will be helpful to assess and envisaged the challenges occurring due to energy transition.